Can ChatGPT provide health information as physicians do? Preliminary findings from a cross-sectional study of online medical consultation - Siqi Luo; Hongyi Qin; Hanlin Li; Cui Huang (Information Research: An International Electronic Journal)
Introduction. ChatGPT has shown promise in medical consultation. This paper presents the preliminary findings of evaluating the capability of ChatGPT in responding to real-world patient questions from a patient point of view, using physician responses as a benchmark.